Educational Diversity
XXVII, 270 p.
Keywords: This collection explores the relationship between new equality regimes and continued societal inequalities, exploring change, ambivalence and resistance specifically in relation to compulsory and post-compulsory education, seeking to more fully situate the educational journeys and experiences of staff and students.